Faktor-Faktor yang Mempengaruhi Tingkat Stress Wanita Usia Subur Penderita Diabetes Melitus di Puskesmas Putri Ayu Kota Jambi - Dewi Nopiska Lilis; Imelda Imelda (Universitas Baiturrahim, 2020)
Abstract Diabetes in women of reproductive age needs to be observed and watched out for. Risks associated with gestational diabetes include pre-natal morbidity and death as well as an increase in chronic cesarean delivery and hypertension in the mother. This study aims to determine the effect of diabetes mellitus on the psychology of WUS in Jambi City in Putri Ayu Health Center in Jambi City in 2019.Data were analyzed using univariate analysis, bivariate with chi square and multivariate using logistic regression analysis. Fertile Age Women (WUS) with higher education have the opportunity not to stress with OR 0.2. WUS with impaired physical health have the opportunity not to stress with OR 4.2. WUS with problem solving skills have the opportunity to not stress with OR 4.2. WUS with high knowledge have a no stress opportunity with OR 0.2. The level of education, physical health, problem solving skills and the level of knowledge of WUS sufferers of diabetes mellitus significantly influence psychology (stress). This research is expected to be able to provide information on knowledge and be able to detect early on the factors that affect the stress level of sufferers of diabetes mellitus by using a scoring scale that can be utilized by health workers in the service and as a reference for diabetes mellitus patients.